ACUTE ATORVASTATIN RECAPTURE THERAPY IN CORONARY ARTERY BYPASS GRAFTING - A. V. Panov; M. L. Gordeev; A. A. Zhloba; T. F. Subbotina; I. V. Suhova; M. I. Buthashvili; I. T. Abesadze; M. Z. Alugishvili; N. L. Lohovinina; K. V. Korzhenevskaya; M. V. Solovyova; L. V. Mihaylova; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To assess the safety of the application of high-dose atorvastatin and its effect on metabolic parameters, such as the total level of nitric oxide and homocysteine in the blood plasma in patients with ischemic heart disease during a coronary artery bypass surgery (CABG).Material and methods. The study included 42 patients with stable effort angina II-IV functional class. A special criterion for selection was the taking atorvastatin at a dose of 20 mg/day for at least 30 days before patient was directed to surgical revascularization of the myocardium. Immediately before the intervention, the dose of atorvastatin was increased to the maximum allowed with subsequent taking of 40 mg/day. Complications after CABG, indicators of lipid metabolism and biochemical safety of statin use were analyzed. The duration of observation of results of the acute atorvastatin recapture therapy was 3 weeks during hospital period. We used modern enzymatic method for nitrogen oxides determination with the application of nitrate reductase. Determination of total homocysteine was performed by high performance liquid chromatography.Results. It was found that atorvastatin 80 mg for 12 hours and 2 hours before CABG in patients previously treated with atorvastatin 20 mg/day is well tolerated and leads to decrease in total levels of nitric oxide by 1.6 (0.18-10.8 ) μmol/l and homocysteine by 0.9 (0.17-2.69) μmol/l (p< 0.05 for both)Conclusion. It is assumed that the metabolic effects of high-dose therapy with atorvastatin may have a positive influence on the immediate postoperative period.